ATH-08 The largest single-centre experience with stent therapy in crohn's disease – a report on outcomes. (June 2019) - Das, Ronit; Singh, Rajeev; Din, Said; Lund, Jonathan; Krishnamoorthy, Rajesh; Hearing, Stephen; Norton, Bernard; Williams, Jessica; Chilkunda, Deepika; Fraser, Catherine; Goddard, Andrew; Cole, Andrew
Abstract : Introduction: Intestinal strictures in Crohn's disease (CD) produce significant morbidity and are the commonest indication for surgery. Removable stent therapy is emerging as an effective, low complication, stricture resolution technique. (Das et al. 2018, Attar et al 2017) We present the clinical outcomes of the largest, single centre series, of CD patients undergoing removable 'self-expanding-metal-stent'(SEMS) therapy for stricture resolution. Methods: Symptomatic CD patients were assessed with MR enterography. Short (≤ 6cm), fibrotic, ileocolonic and anastomotic strictures were approved for stent therapy from an IBD MDT setting. Strictures were assessed, and only endoscopically impassable strictures treated. Inaccessible or inflammatory strictures were excluded. The Hannaro Diagmed 'HRC-20–080–230', partially covered SEMS was deployed under endoscopic and fluoroscopic guidance. Stent retrieval occurred at 6–10 days post insertion. Clinical IBD data was collected. Post-stenting follow-up was conducted, and therapeutic success assessed with validated tools (CDAI/HBI). Results: Twenty-six patients were considered for stenting. Six patients were excluded based on endoscopic criteria. Twenty-two stents were placed for 20 patients. Stent deployment and retrieval was successful in 100% of cases when attempted. Ninety percent (18 of 20) of strictures were anastomotic. Patient characteristics are detailed in figure 1. Symptom improvement or resolution was noted in 84.6% of patients at follow up. Re-stenting was needed in two patients, with a single repeat procedure required within 12 months. Across all stenting episodes 5 adverse events were noted (2 episodes of stent related discomfort/3 asymptomatic stent migrations). There were no bleeding events, perforations or any need for emergency surgery. None of the cohort have required stricture related surgery on extended follow up (Range: 2 – 42 months). Conclusions: In this series, removable SEMS therapy for ileocolonic CD strictures was found to be technically successful and clinically efficacious. The absence of perforation events and the complete lack of need for any stricture related surgery are both notable. The apparent efficacy, safety, long term benefit and low re-intervention rate with SEMS therapy in CD, merits further large-scale trial investigation in direct comparison with other modalities. References: Attar A, et al. New anti-migration extractible metal stents for Crohn's disease strictures. Journal of Crohn's & Colitis 2017.11: S389–S390. Das R, et al. Treating ileocolonic Crohn's strictures with removable. Gut . 2018:67:A55-A56.